The Reasons, Barriers and Effects of the Implementation of Controlling in the Managers' Opinions in The Heat Plant MPEC - Kowalewski , Mirosław; Lelusz , Henryk (Studia Oeconomica Posnaniensia, 2018)
The goal of the research was to determine the reasons, barriers and effects of the implementation of controlling in the heat plant MPEC. The survey was conducted in 2016 and 15 mid-level managers (department directors) of the company participated in it. The research showed that in the managers' opinion the key reason for implementation of controlling in the company was a need to systemize the processes of planning and analyses, and the main barrier was insufficient knowledge of controlling among employees. The most important positive result of the implementation of controlling in the company was an improvement of allocation of tasks and targets among the organizational units, as well as, an increase of employees' professionalism.